The Fusion Protein Signal-Peptide-Coding Region of Canine Distemper Virus: a Useful Tool for Phylogenetic Reconstruction and Lineage Identification - Sarute, Nicolás (2013)
Canine distemper virus (CDV) (Paramyxoviridae, Morbillivirus) is the etiologic agent of a multisystemic infectious disease affecting all the terrestrial carnivore families, with high incidence and mortality in domestic dogs. The hemagglutinin (H) gene has been widely employed to characterize field strains, permitting the identification of the nine CDV lineages worldwide. Recently, it has been established that the fusion protein signal peptide coding region (Fsp) is extremely variable, suggesting its usefulness for characterization studies. However, the divergence among global strains and its phylogenetic resolution has not been evaluated yet. Herein, we constructed two datasets with the Fsp coding region and H gene sequences of the same strains belonging to eight CDV lineages, and used them to compare both genomic regions through phylogenetic and likelihood mapping analyses. The phylogenetic analysis revealed that both datasets clustered the strains in eight CDVs lineages. The amino acid divergence inter-lineages showed values for Fsp peptide four-fold higher than the H protein. The likelihood mapping study revealed that both datasets displayed strong phylogenetic signals in the region of well-resolved topology. These features indicated that the Fsp coding region is useful for evolutionary analysis as it allows the straightforward identification of CDV lineages.